Controlling in networking organisations - the concept and assumptions = Controlling w organizacjach sieciowych - koncepcja i założenia - Bieńkowska, Agnieszka; Zabłocka-Kluczka, Anna (Zielona Góra: Faculty of Economics and Management Press)
The article contains the characterisation of the issue and features of a networking organisation. In the context of a specific manner of cooperation among organisations-partners in the network there has been indicated a great need for coordination of activities of particular entities for the purpose of meeting the arranged objectives and controlling has been proposed as a method supporting effective networking organisation management.
Keywords: controlling; organizacja sieciowa; sieć współpracy; networking organisation; network of cooperation